PENGARUH PENAMBAHAN UREA DAN SULFUR PADA LIMBAH PADAT BIOETANOL YANG DIFERMENTASI EM-4 TERHADAP KANDUNGAN PROTEIN DAN SERAT KASAR - Yani Suryani; Iman Hernaman; Ningsih Ningsih (JURNAL ILMIAH PETERNAKAN TERPADU, 2017)
Cassava processing into bioethanol potentially generates waste as animal feed, but the content of nutrients is still low. This research aims to discover effect of urea and sulfur addition in solid waste bioethanol fermented by EM-4 on contents of crude protein and fiber. The research used the experimental methods with completely randomized design, factorial pattern 3 × 3 with 3 time of replicates. The first factor, supplementation of Nitrogen is Urea (N1=0%, N2=1,5%, N3=3%) and the second factor is supplementation of sulfur (S1=0%, S2=0,02%, S3=0,04%). Based on the results of variance analysis showed that there is an interaction between urea with sulfur on content of protein crude, but not on fiber crude. Addition of each urea and sulfur showed that the content of crude protein was increased (P<0,05) and the level of crude fiber (P<0,05) was decreased. Fermentation along 4 day on treatment of urea 3% and sulfur 0,04% produce crude protein and fiber of 14,44% and 6,97%, respectively. Conclusion, addition of urea 3% and sulfur 0,04% give the good results.Keywords: Bioethanol, EM-4 (Efective Microorganisms4), Crude Protein, Crude Fiber, Sulfur and Urea